Non-Vitamin K Antagonist Oral Anticoagulants in Differentiated Approach to the Use in Cardiological Practice: Literature Review - Larysa A. Vozniuk; Olga V. Dzekan; Sergii O. Siromakha (Ukrainian Journal of Cardiovascular Surgery, 2023)
Non-vitamin K antagonist oral anticoagulants (novel oral anticoagulants, NOACs) are important pharmaceuticals for prevention of stroke and systemic embolism in non-valvular atrial fibrillation patients. Vitamin K antagonist warfarin usage is limited due to its pharmacokinetic and pharmacodynamic parameters. In modern conditions, NOACs are widely used. This literature review includes the most interesting clinical studies where anticoagulants were used. Main pharmacological properties of non-vitamin K antagonist oral anticoagulants have been investigated in these clinical studies.The aim. To answer the question about which anticoagulant is preferable for use in particular clinical situation.Results. In order to prevent venous thrombosis, conservative and surgical treatment is used. It is the use of anticoagulants during conservative therapy that allows to extend the life expectancy of patients at high risk of thrombosis. Unlike warfarin, the use of NOACs helps to avoid high risk of bleeding. Drugs of this group have short half-life, standard dosage, and predicted pharmacological effect.Conclusions. New data about comparative efficacy and safety of treatment with NOACs (dabigatran, rivaroxaban, edoxaban, apixaban) in order to prevent thromboembolism in patients with atrial fibrillation are presented. The peculiarities of anticoagulant therapy in elderly patients, patients with coronary artery disease, atrial fibrillation, chronic kidney disease, patients in pre- and postoperative periods are discussed. Prolonged study of drugs of this group will enable doctors to use them without endangering the patients’ lives. NOACs, despite obtained data about their effectiveness and safety, in our opinion, deserve attention and require further study.